Torsional ultrasound mode versus combined torsional and conventional ultrasound mode phacoemulsification for eyes with hard cataract - Fakhry MA; El Shazly MI (Clinical Ophthalmology, 2011)
Mohamed A Fakhry1,2, Malak I El Shazly11Department of Ophthalmology, Kasr El Aini Hospital, Cairo University, Cairo, Egypt; 2Cataract and Refractive Consultant, International Eye Hospital, Cairo, EgyptPurpose: To compare torsional versus combined torsional and conventional ultrasound modes in hard cataract surgery regarding ultrasound energy and time and effect on corneal endothelium.Settings: Kasr El Aini hospital, Cairo University, and International Eye Hospital, Cairo, Egypt.Methodology: Ninety-eight eyes of 63 patients were enrolled in this prospective comparative randomized masked clinical study. All eyes had nuclear cataracts of grades III and IV using the Lens Opacities Classification System III (LOCS III). Two groups were included, each having an equal number of eyes (49). The treatment for group A was combined torsional and conventional US mode phacoemulsification, and for group B torsional US mode phacoemulsification only. Pre- and post-operative assessments included best corrected visual acuity (BCVA), intraocular pressure (IOP), slit-lamp evaluation, and fundoscopic evaluation. Endothelial cell density (ECD) and central corneal thickness (CCT) were measured preoperatively, 1 day, 7 days, and 1 month postoperatively. All eyes were operated on using the Alcon Infiniti System (Alcon, Fort Worth, TX) with the quick chop technique. All eyes were implanted with AcrySof SA60AT (Alcon) intraocular lens (IOL). The main phaco outcome parameters included the mean ultrasound time (UST), the mean cumulative dissipated energy (CDE), and the percent of average torsional amplitude in position 3 (%TUSiP3).Results: Improvement in BCVA was statistically significant in both groups (P < 0.001). Comparing UST and CDE for both groups revealed results favoring the pure torsional group (P = 0.002 and P < 0.001 for UST; P = 0.058 and P = 0.009 for CDE). As for %TUSiP3, readings were higher for the pure torsional group (P = 0.03 and P = 0.01). All changes of CCT, and ECD over time were found statistically significant using one-way ANOVA testing (P < 0.001).Conclusion: Both modes are safe in hard cataract surgery, however the pure torsional mode showed less US energy used.Keywords: torsional, cumulative dissipated energy, cataract